(untitled) (Conferencea, 2022)
A number of United Nations-supported technical vocational education (TKT) programs are aimed at specific disadvantaged groups of the population, such as young women and young people in poor rural regions, and these programs represent the main focus of UN experience documented in case studies. TKT programs in Singapore the Singapore Institute of technical education (tti) has extensive experience in adapting to changes in the technology and labor market and continuously beneficial training of young people skilled workers for businesses.